Photosynthetic and grain yield responses to intercropping of two common bean lines with maize under two types of fertilizer applications in the colombian amazon region - Suárez, Juan Carlos; Anzola, José Alexander; Contreras, Amara Tatiana; Salas, Dina Luz; Vanegas, José Iván; Urban, Milan Oldřich; Beebe, Stephen E.; Rao, Idupulapati M. (Elsevier, 2022)
Acid soils in the Amazon region are characterized by low fertility and high aluminum saturation causing reduced crop yields. Improving genetic adaptation of crop genotypes together with suitable agronomic management practices can mitigate the impact on crop production in acid soils. The objective of the present study was to determine the photosynthetic and grain yield responses of two common bean lines to intercropping with maize under two types of fertilizer applications in the Colombian Amazon region. A randomized complete block design (RCBD) with 3 replications in a nested trifactorial arrangement was used consisting of two advanced bean lines of BFS 10 and ALB 121 (main plots); three cropping system patterns of monoculture, intercropping pattern 1, intercropping pattern 2 (subplots); and two types of fertilizer applications, chemical and organic (sub-subplots) for a total of 12 treatments. The experiment was conducted in two growing seasons and the effects of the treatments were evaluated during two growth stages within a cropping season. Measurements included photo- synthetic gas exchange characteristics, chlorophyll fluorescence, specific leaf area, viability of pollen and grain yield. Mean values from two growing seasons were presented. Photosynthetic response of BFS 10 was superior to ALB 121 under both monoculture and intercropping patterns with either chemical or organic fertilizer appli- cation. Both bean lines showed an increase in apparent quantum efficiency and maximum rate of ribulose-1, 5- bisphosphate carboxylase/oxygenase (RuBisCO) carboxylation (Vcmax) during pod filling growth stage when grown in association with maize, particularly with organic fertilizer application. Small farmers in the Amazon region can benefit from either one of the two bean lines by growing them as intercrops with maize, using organic fertilizer application.